STRATEGI PENINGKATAN KUALITAS PELAYANAN BUS TRANS SIGINJAI DI PROVINSI JAMBI (Strategy For Increasing The Quality Of Bus Trans Siginjai Service In Jambi Province) - Vinni Aprilianti Aprilianti; Asti Harkeni (Balitbangda Provinsi Jambi, 2023)
Abstract Research on Trans Siginjai Bus (BTS) services to the community aims to develop strategies to improve the quality of Trans Siginjai Bus services as an effort to make improvements in accordance with the expectations of the people in Jambi Province. This research uses a descriptive approach with mixed methods methods, namely combining qualitative and quantitative methods). The study distributed questionnaires to BTS passengers on the two existing corridors, namely the Mandalo route and the Route to Sengeti as many as 243 with 126 respondents using the corridor I bus service and 117 samples in corridor II. Analysis using Importance Performance Analysis (IPA). The results obtained are that there are 9 indicators in the policy priority quadrant in an effort to improve the quality of Trans Siginjai Bus (BTS) services by the Jambi Province Transportation Service, namely the distance between bus stops so that they can accommodate the needs of Trans Siginjai Bus service users, the frequency of arrivals during peak hours so that they can be accelerated , Bus operating hours are adjusted to user activities, arrival schedules are on time, departure schedules are on time, Trans Siginjai users/passengers can easily change to other modes of transportation, schedule and fare information is available at bus stops, schedule and fare information is available on the Bus; and Trans Siginjai Bus routes to suit user needs. Keywords:Trans Siginjai Bus, Services, Routes, Importance Performance Analysis. Abstrak Penelitian pelayanan Bus Trans Siginjai (BTS) kepada masyarakat bertujuan untuk menyusun strategi peningkatan kualitas pelayanan Bus Trans Siginjai sebagai upaya melakukan perbaikan-perbaikan sesuai dengan harapan masyarakat di Provinsi Jambi. Penelitian menggunakan pendekatan deskriptif dengan metode mixed methods yaitu menggabungkan metode secara kualitatif dan kuantitatif). Penelitian menyebarkan kuisioner kepada penumpang BTS pada dua koridor yang ada yaitu rut eke Mandalo dan Rute ke Sengeti sebanyak 243 dengan responden yang menggunakan layanan bus koridor I sebanyak 126 orang dan sampel pada koridor II sebanyak 117 orang. Analisis menggunakan Importance Performance Analysis (IPA). Hasil yang diperoleh yaitu ada 9 indikator dalam kuadran prioritas kebijakan dalam upaya peningkatan kualitas pelayanan Bus Trans Siginjai (BTS) oleh Dinas Perhubungan Provinsi Jambi, yaitu jarak antar halte agar dapat mengakomodir kebutuhan pengguna layanan Bus Trans Siginjai, frekuensi kedatangan pada jam sibuk agar dapat dipercepat, jam operasi Bus disesuaikan dengan aktivitas pengguna, jadwal kedatangan tepat waktu, jadwal keberangkatan tepat waktu, pengguna/penumpang Trans Siginjai mudah dalam berganti moda transportasi lainnya, tersedia informasi jadwal dan tarif di halte, tersedia informasi jadwal dan tarif di dalam Bus; dan trayek Bus Trans Siginjai agar disesuaikan dengan kebutuhan pengguna. Kata kunci: Bis Trans Siginjai, Pelayanan, Trayek, Importance Performance Analysis